(untitled) (Bangladesh Journal of Botany, 2021)
Antimicrobial activities of deoiled seed kernel (mechanically pressed), fruit coat and seed coat of Jatropha curcas Linn. collected from two regions (Bannu and Peshawar) of Pakistan were investigated. The antimicrobial activities were carried out against Klebsiella pneumoniae (ATCC 43816), Escherichia coli (ATCC 10536), Staphylococcus aureus (ATCC 6538), Bacillus subtilis (ATCC 6633) and two clinical fungal isolates Aspergillus fumigatus and Candida albicans using agar well diffusion method. The antibacterial activities of Peshawar sample were found to be higher than Bannu, against selected strains. While antifungal activities of both samples were similar. Highest zone of inhibition 31.5 ± 0.7 mm was exhibited by n-hexane extract of deoiled seed kernel of Peshawar sample against Bacillus subtilis (ATCC 6633). The minimum inhibitory concentration of ethanolic extracts of deoiled seed kernel and seed coat of Peshawar sample was 31.25 - 25 mg/ml. Whereas, minimum inhibitory concentration of ethanolic and n-hexane extracts of Bannu sample was 62.5 - 125 mg/ml. The results suggested that antimicrobial potential of J. curcas Linn. varied with geographical distribution. The investigation of different varieties of medicinal plants belonging to the same species will greatly enhance the chances of best pharmaceuticals discovery. Bangladesh J. Bot. 50(2): 219-226, 2021 (June)